Exploring the emotional geographies of EFL students’ participation in group assignments: A narrative inquiry - Wahyuni, Sri; Heriyawati, Dwi Fita; Ubaidillah, M. Faruq; Prabjandee, Denchai (Journal of Research on English and Language Learning (J-REaLL), 2025)
Research on emotional geographies in EFL learning has been extensively carried out. However, the studies have mostly focused on the context of teachers' rather than students' emotional geographies. Informed by the emotional geographies framework, this study investigated the ways in which three EFL students construct and experience their emotional geographies while engaging in group work assignments. It specifically focuses on the participants’ past, present, and future experiences of participating in group work and how they deal with emotional issues. The study employed a narrative inquiry to elicit participants' lived experiences with in-depth interviews to collect the data. This method is considered appropriate for research designs that allow exploration of the emotional dimensions and experiences of participants in their past, present, and future through storytelling. For the data collection, this study conducted interviews in two ways, including direct interviews and online interviews. The findings show various negative emotional geographies experienced by EFL students in their group assignment participation, such as frustration, anxiety, insecurity, and disappointment. It also reveals that participants overcome those emotional issues in several ways, including adjusting their personalities, taking on more responsibility than others, and asking for help from third parties. The limitation of this study is the single data collection method, namely, interviews, which may affect the generalizability of the data. This study suggests more supportive learning environments by providing more information about group emotions and dynamics to students. Future research is encouraged to explore EFL students’ emotions in different contexts.